Achieving enhanced diagnostic precision in endometrial lesion analysis through a data enhancement framework - Luo, Yi; Yang, Meiyi; Liu, Xiaoying; Qin, Liufeng; Yu, Zhengjun; Gao, Yunxia; Xu, Xia; Zha, Guofen; Zhu, Xuehua; Chen, Gang; Wang, Xue; Cao, Lulu; et al. (Frontiers in Oncology, 2024)
ObjectiveThe aim of this study was to enhance the precision of categorization of endometrial lesions in ultrasound images via a data enhancement framework based on deep learning (DL), through addressing diagnostic accuracy challenges, contributing to future research.Materials and methodsUltrasound image datasets from 734 patients across six hospitals were collected. A data enhancement framework, including image features cleaning and soften label, was devised and validated across multiple DL models, including ResNet50, DenseNet169, DenseNet201, and ViT-B. A hybrid model, integrating convolutional neural network and transformer architectures for optimal performance, to predict lesion types was developed.ResultsImplementation of our novel strategies resulted in a substantial enhancement in model accuracy. The ensemble model achieved accuracy and macro-area under the receiver operating characteristic curve values of 0.809 of 0.911, respectively, underscoring the potential for use of DL in endometrial lesion ultrasound image classification.ConclusionWe successfully developed a data enhancement framework to accurately classify endometrial lesions in ultrasound images. Integration of anomaly detection, data cleaning, and soften label strategies enhanced the comprehension of lesion image features by the model, thereby boosting its classification capacity. Our research offers valuable insights for future studies and lays the foundation for creation of more precise diagnostic tools.